Ruxolitinib as a therapy choice for refractory pruritus in a patient with essential thrombocythemia with CALR mutation - Kubra Cerci; Pusem Patir (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2023)
Refractory pruritus associated with Essential Thrombocythemia (ET) is rare. Herein, we present the first report of resistant pruritus responsive to ruxolitinib in an ET patient with a calreticulin mutation.